Ergonomics intervention on manual handling at strider area in an aircraft manufacturing company - Ang, Nian Qi (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This main objective of the project is to solve ergonomics issue on manual handing roll material at Strider Area need of Aerospace Composites Malaysia Sdn Bhd. The workers form Strider Ares need to handle heavy roll materials which weight from 23 kg to 113 kg everyday base on the usages of the material. Two main ergonomics risk factors occur during the task are forceful exertion and awkward posture.